2012
DOI: 10.3109/03014460.2012.692810
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profiles in the non-pregnant state predict offspring birth weight at Cebu: Evidence for inter-generational effects of low grade inflammation

Abstract: Background Although maternal infection and inflammation during pregnancy can adversely affect offspring birth weight (BW), whether low grade inflammation in the non-pregnant state predicts BW is unknown. Aim Evaluate relationships between offspring BW and pro- and anti-inflammatory factors measured in parous but non-pregnant women. Subjects and methods Data come from 234 parous Filipino females (21.5 ± 0.3 yr) in the Cebu Longitudinal Health and Nutrition Survey, a population-based birth cohort in Metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We recently reported that inflammatory markers measured outside of pregnancy have modest relationships with birth outcomes in this sample (Kuzawa et al, 2012), suggesting that differences in basal inflammatory regulation could impact offspring birth outcomes and potentially have long-term impacts on health. Although the present analyses were cross-sectional and thus incapable of addressing impacts on offspring, in the future we hope to longitudinally investigate these questions at Cebu.…”
Section: Discussionmentioning
confidence: 87%
“…We recently reported that inflammatory markers measured outside of pregnancy have modest relationships with birth outcomes in this sample (Kuzawa et al, 2012), suggesting that differences in basal inflammatory regulation could impact offspring birth outcomes and potentially have long-term impacts on health. Although the present analyses were cross-sectional and thus incapable of addressing impacts on offspring, in the future we hope to longitudinally investigate these questions at Cebu.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous factors aside from microbial exposure have been shown to induce systemic maternal inflammation and/or chorioamnionitis, including nutritional and psychosocial factors (reviewed in ( 140 )). Of great concern are the observations linking perinatal inflammation from various causes with immune dysfunction and abnormal stress responses, not only in the immediate postnatal period but possibly throughout life or even into the next generation ( 145 ). Thus, the importance of advancing knowledge of perinatal inflammation and its causes cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…; Crompton & Nesheim ; Kuzawa et al . ). Adolescent pregnancy interferes with nutrient availability to the foetus due to the competing demands of ongoing maternal growth (Prakash et al .…”
Section: Causes Of Stunted Growth and Developmentmentioning
confidence: 97%